Avaliação de cultivares de soja [Glycine max (L.) Merrill] quanto à tolerância à Rhizoctonia solani - Ben, Cássio Alberto Vielmo (2015)
The objective of this study was to evaluate the genetic resistance of cultivars for the possible damage caused by Rhizoctonia solani in controlled humidity conditions. For this, the work was divided into parts, which began from the get the pathogen identified in the AG-4 anastomosis group, mainly responsible for causing rot the root system and soybean seedling damping-off. Then the spread was performed in laboratory, cultured in petri dishes, and after standing in a culture medium using corn flour, sand and distilled water, which was evaluated inoculum different doses (0, 5, 15, 25, 40g) in order to adjust the conditions for the damage. For the tests in the greenhouse, all experimental units were formed by a polyethylene tray with a capacity of 2.5 L, containing sterile sand 5.5Kg, with additional fertilizers and 80% of field capacity. For the evaluation of inoculum doses opening was arranged in 5 rows in each tray and the treatments applied to the quantities evaluated with 4 repeated, with a repetition of each tray. Two days after inoculation, 50 seeds were sown in each tray. This procedure was performed twice, each time with a different cultivar. We evaluated the germination and the damage to the root system, considered the end that 25g enough to cause damage. Evaluations were carried germination and sanity 40 cultivars which 10 were selected to be used in the final assay. Finally, selected cultivars were evaluated in a greenhouse in two exposure to the pathogen, with and without R. solani, forming a bi factorial (10x2) with 20 treatments. Emergence were evaluated, and tipping in pre emergency, and morphological analyzes, at 28 DAS, plant height was evaluated, fresh and shoot dry, fresh and dry weight of root and root length and volume. For emergencies, there was no significant difference between cultivars without inoculation, however, in inoculum exposure conditions NS 5959 cultivars, TEC 6070 IRGA and ZIP 64 proved superior. To rot in pre-emergency assessments to grow with higher rates was the BMX NIB, with 53.86% of the seeds. For seedling height, the earliest cultivars showed the highest values, with the NS 5959 and V-TOP with the best rates. Both fresh weight as the shoot dry mass did not differ among cultivars and treatments. The analysis of the root system showed better results for cultivars IRGA TEC 6070, NS 5959, CEP 64 and V-TOP to root length, V-TOP and TEC IRGA 6070 for fresh and dry weight of root and root volume. Pathogen confirmation evaluation, the result was positive for all analyzes. In conclusion, you can see very vulnerable cultivars to R. solani, which is an important pathogen found in lowland conditions and can cause major yield losses.